Functionalization of liquid-exfoliated two-dimensional 2H-MoS2 - Backes, Claudia; Berner, Nina C.; Chen, Xin; Lafargue, Paul; Laplace, Pierre; Freeley, Mark; Duesberg, Georg S.; Coleman, Jonathan N.; Mcdonald, Aidan R. (Angewandte Chemie International Edition, 2015)
Layered two-dimensional (2D) inorganic transition-metal dichalchogenides (TMDs) have attracted great interest as a result of their potential application in optoelectronics, catalysis, and medicine. However, methods to functionalize and process such 2D TMDs remain scarce. We have established a facile route towards functionalized layered MoS2. We found that the reaction of liquid-exfoliated 2D MoS2, with M(OAc)2 salts (M = Ni, Cu, Zn; OAc = acetate) yielded functionalized MoS2-M(OAc)2 materials. Importantly, this method furnished the 2H-polytype of MoS2 which is a semi-conductor. X-ray photoelectron spectroscopy (XPS), diffuse reflectance infrared Fourier transform spectroscopy (DRIFT-IR), and thermogravimetric analysis (TGA) provide strong evidence for the coordination of MoS2 surface sulfur atoms to the M(OAc)2 salt. Interestingly, functionalization of 2H-MoS2allows for its dispersion/processing in more conventional laboratory solvents.
Created from Fastlane, Scopus look-up
Keywords: 2D materials; Carboxylate ligands; Liquid exfoliation; Surface functionalization; Transition-metal dichalcogenides